1981
DOI: 10.1111/j.1365-2273.1981.tb01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer variability in the clinical and radiological assessment of adenoid size, and the correlation with adenoid volume

Abstract: Forty-six children were independently assessed with respect to size of adenoids and other clinical features by 3 observers of differing experience. Similar assessment was made of adenoid area and post-nasal-space airway from lateral cephalometric X-rays. The inter-observer agreement for these findings has been calculated. Absolute agreement between observers for the assessments is poor and in some instances this is related to clinical experience. In relative terms the agreement is more satisfactory. A nasal ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 10 publications
5
40
1
1
Order By: Relevance
“…26 The degree of correlation (Kendall test) was very similar among the different radiographic measurements and nasal endoscopy (r 5 0.67-0.68). Other authors, 29,30 despite using other methods for comparison, found similar correlation coefficients. The area under the ROC curve of 0.84 suggests a strong correlation between diagnosis made according to LCR and FFE.…”
Section: Discussionsupporting
confidence: 50%
“…26 The degree of correlation (Kendall test) was very similar among the different radiographic measurements and nasal endoscopy (r 5 0.67-0.68). Other authors, 29,30 despite using other methods for comparison, found similar correlation coefficients. The area under the ROC curve of 0.84 suggests a strong correlation between diagnosis made according to LCR and FFE.…”
Section: Discussionsupporting
confidence: 50%
“…But the residual nasopharyngeal airway in the symptomatic children was significantly smaller than that in asymptomatic children [18]. This observation has been confirmed by many authors [6,14,19]. The degree of nasopharyngeal airway obstruction was shown to be a more reliable parameter than the actual size or volume of resected adenoids in the evaluation of adenoidal obstruction severity [12].…”
Section: Discussionsupporting
confidence: 59%
“…Many previous studies, however, have used subjectively graded adenoid sizes or adenoid volumes removed at surgery as gold standards to which cephalometric measurements have been compared. [14][15][16][17] The development of SDB depends more on a decreased upper airway size than on the absolute size of the lymphoid tissue. 18 For this reason the actual size of pharyngeal airway should be used as a gold standard comparison when evaluating methods for diagnosing obstructed airways.…”
Section: Discussionmentioning
confidence: 99%